2020
DOI: 10.14295/vittalle.v32i1.9644
|View full text |Cite
|
Sign up to set email alerts
|

Incidence analysis of human leptospirosis in Brazil

Abstract: Leptospirosis is a neglected infectious disease that affects humans and animals with a higher incidence in the tropics and subtropics. In that context, the aim of this study was to describe the temporal distribution of the epidemiology and sociodemographic factors of human leptospirosis in Brazil. The analysis conducted in this study was based to age, gender, area, schooling, region and skin colour reported by Ministry of Health from National Disease Notification System (SINAN) and National Survey of Household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…Consistent a study from Netherlands reported that those aged 45-64 years were found to be significantly associated with leptospirosis incidence (Rood et al, 2017). Similar to a study from Brazil that showed that the most cases of leptospirosis occurred in individuals aged from 20-39 years old, followed by those aged 40-59 years old (Silveira et al, 2020), a study from Malaysia reported that the most cases of leptospirosis found in aged 30-39 years (Benacer et al, 2016), a study from Mexico reported that the most cases occurred in aged 25-44 years (Sánchez-Montes et al, 2015). These age groups are at increased risk due to occupational exposure (Silveira et al, 2020), which is the working-aged was probably due to a frequent exposure with environmental risk factors for leptospirosis higher than other age group, which the study from Kuantan, Malaysia reported the aged 18-29 years had a preventive practice of leptospirosis better than the other age group (Aidid et al, 2018).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent a study from Netherlands reported that those aged 45-64 years were found to be significantly associated with leptospirosis incidence (Rood et al, 2017). Similar to a study from Brazil that showed that the most cases of leptospirosis occurred in individuals aged from 20-39 years old, followed by those aged 40-59 years old (Silveira et al, 2020), a study from Malaysia reported that the most cases of leptospirosis found in aged 30-39 years (Benacer et al, 2016), a study from Mexico reported that the most cases occurred in aged 25-44 years (Sánchez-Montes et al, 2015). These age groups are at increased risk due to occupational exposure (Silveira et al, 2020), which is the working-aged was probably due to a frequent exposure with environmental risk factors for leptospirosis higher than other age group, which the study from Kuantan, Malaysia reported the aged 18-29 years had a preventive practice of leptospirosis better than the other age group (Aidid et al, 2018).…”
Section: Resultssupporting
confidence: 78%
“…Additionally, there was a nearly significant linear relationship between higher household elevation and lower infection risk for each 10 meters increase in elevation (Hagan et al, 2016). Different from a study in Brazil reported that the local profile of human leptospirosis was predominantly associated with urban areas (Santos et al, 2017 andSilveira et al, 2020).…”
Section: Resultsmentioning
confidence: 68%